What is at the End of Crisis? Medium-term Scenarios for the Development of World and Russian Economies - Natalia Akindinova; Maxim Petronevich (Foresight and STI Governance)
The authors of the paper looks at possible scenarios of Russia’s economic development in the nearest three years. Such issues as economic performance in 2010, ruble rate and Russian financial tendencies are touched upon. Besides, the paper reports on scenario analysis of Russian economics in context of the world processes. This analysis was the base for the authors’ conclusions on medium-term development prospects.